Value-Based Adoption Model to Increase Purchase Intention in the Use of Virtual Try-On - Harjati, Fitriana; Masnita, Yolanda; Kurniawati, Kurniawati (Almana : Jurnal Manajemen dan Bisnis, 2025)
Abstract: The rapid advancement of e-commerce, driven by the integration of Augmented Reality (AR) Virtual Try-On technology, has significantly transformed consumer purchasing behavior. This study explores the impact of AR-based Virtual Try-On on purchase intention using the Value-Based Adoption Model (VAM) framework. A quantitative approach with Structural Equation Modeling (SEM) was applied to analyze data from 318 respondents through an online survey. The respondents consisted of Generation Y (1981-1996) and Generation Z (1997-2012), representing diverse demographic backgrounds. The findings reveal that Perceived Value, Perceived Ease of Use, Perceived Usefulness, Perceived Enjoyment, and Technology Informativeness positively and significantly affect purchase intention. Perceived Value, as the core of VAM, reflects the balance between perceived benefits and sacrifices in adopting new technology. Meanwhile, other factors, such as Perceived Ease of Use and Perceived Usefulness, are adapted from the Technology Acceptance Model (TAM) to offer a broader perspective on consumer adoption of AR Virtual Try-On. This technology enhances user experience, reduces perceived product risk, and provides substantial added value for consumers. The study concludes that implementing AR-based Virtual Try-On is a crucial innovation to boost consumer engagement and loyalty, ultimately driving the growth and competitive advantage of e-commerce platforms, particularly in Indonesia.